Seroprevalence of Feline Heartworm in Spain: Completing the Epidemiological Puzzle of a Neglected Disease in the Cat - Montoya-Alonso, José Alberto; García Rodríguez, Sara Nieves; Carretón, Elena; Rodríguez Escolar, Iván; Costa-Rodríguez, Noelia; Matos, Jorge Isidoro; Morchón, Rodrigo (Frontiers in Veterinary Science, 2022)
Feline heartworm is a vector-borne zoonotic disease caused by Dirofilaria immitis. It is a cosmopolitan disease that is continuously expanding. Spain is considered an endemic country; however, although there are many published studies in dogs, feline heartworm has been poorly studied in this country. Thus, the objective was to analyse the exposure to D. immitis throughout Spain to complete the epidemiological map in the feline species. For this, 6588 feline serum samples were analysed for the presence of D. immitis antigens and antibodies against D. immitis and Wolbachia. The results were analysed according to sex, age, breed, habitat, origin (owned or shelter cats), presence of clinical signs, use of preventive, location and climatology. The results showed a prevalence of 0.5% and a seroprevalence of 9.4%. The highest antibody seroprevalences were reported in the Canary Islands and the Balearic Islands (19.2% and 16%, respectively), as well as in the autonomous communities located on the Mediterranean coast (9.2-11.2%). Seropositive cats were found in both indoor and outdoor cats, and from 6 months of age. Furthermore, only 5.8% of cats received regular prophylactic treatment. The results show that feline dirofilariasis is widely distributed throughout the national territory and corroborate that, where infected dogs are present, there are cats exposed to the parasite. It is necessary to implement efficient awareness and prophylaxis measures to control the incidence and expansion of feline heartworm in Spain